Managing financial risks from global to local - Clark, Gordon L.; Dixon, Adam D.; Monk, Ashby H. B. 1976- (Ashby Henry Benning). (Oxford Oxford University Press, 2009)
This title brings together a group of leading scholars from a range of disciplines to formulate a more holistic understanding of financial risk by rooting it in different environments, spatial scales, and disciplines.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Financial risk management